KONSEP PENGELOLAAN BAGAN PANCANG NELAYAN SECARA BERKELANJUTAN DI KELURAHAN SIBOLGA ILIR KECAMATAN SIBOLGA UTARA KOTA SIBOLGA - Sinaga, Nora Juniarti (PERSPEKTIF, 2014)
The concept of the management of the fishing pole so that the chart can be viewed through three perspectives, namely sustainable economically, socially and ecologically sustainable. This research aims to identify what institutions are involved in the management of a fishing pole in Sibolga Ilir village, Sibolga Utara district Sibolga city. This research is a descriptive study of qualitative. The technique of collecting data through observation, interview, spreading the now, as well as the study of librarianship. The results of research is an institution managing a fishing pole is a chart Department of marine, Fishery and animal husbandry Sibolga Port Administrator, Sibolga and Sibolga Ilir Village. This research is a descriptive study of qualitative nature. The technique of collecting data through observation, interview, spreading the now, as well as the study of librarianship. The results of research is the concept of management of the chart of the stake in Kelurahan of Sibolga Sub-district Ilir Sibolga Utara, Sibolga unsustainable due to the not yet established boundaries and the safe zone to the establishment of the fishing pole, use chart chart of excessive fishing pole that gives rise to an indirect impact on the structure of the tropical rainforest and the direct impact on the habitat.